2021
DOI: 10.7759/cureus.18634
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Blood Parameters and Comorbidities on Three-Month Mortality in Elderly Patients With Hip Fracture

Abstract: BackgroundKnowing the factors that increase the risk of death in patients with hip fractures will help us to take precautions and intervene when necessary in the pre-and postoperative periods. Therefore, it is important to have inexpensive and practical biomarkers that can predict postoperative complications and mortality. The present study aimed to identify the factors that contribute to early mortality in elderly patients with hip fractures in the first three months after trauma, as well as the parameters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In human patients, systemic lactate concentration is a prognostic indicator and can be used to predict death after a hip or pertrochanteric fracture. [26][27][28][29][30] The present study had not found a similar association between hyperlactatemia and death after a long-bone fracture in cattle. This difference is probably because the lactate concentration was mainly used to assess ischemia and hypoxia at the whole-body level of human patients more severely compromised than the cattle patients included in our study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In human patients, systemic lactate concentration is a prognostic indicator and can be used to predict death after a hip or pertrochanteric fracture. [26][27][28][29][30] The present study had not found a similar association between hyperlactatemia and death after a long-bone fracture in cattle. This difference is probably because the lactate concentration was mainly used to assess ischemia and hypoxia at the whole-body level of human patients more severely compromised than the cattle patients included in our study.…”
Section: Discussionmentioning
confidence: 58%
“…[23][24][25] Lactate concentration can be used as a prognostic indicator and predict death in human patients diagnosed with hip or pertrochanteric fractures. [26][27][28][29][30] Additionally, long-bone and pelvic fracture repair in human patients with increased lactate concentration has been associated with greater postoperative morbidity. 31,32 The determination of whether lactate concentrations are of prognostic value in cattle diagnosed with a long-bone fracture has not been studied previously.…”
Section: Clinical Relevancementioning
confidence: 99%
“…(37) According to the literature, a high level of creatinine is one of the markers of the risk of early mortality in elderly patients with fractures of the proximal femur. (38) There were no differences in creatinine levels in SHR rats compared to healthy Wistar rats.…”
Section: Groups Groupsmentioning
confidence: 85%
“…Associations have been found between the surgical approach 6 , Charlson Comorbidity Index 7 , delay from admission to surgery 8 , body mass index 9 , anticoagulant consumption 10 12 , type of anesthesia 13 and mortality or complications following hip fractures surgery have been previously discussed. Pre-operative factors like anemia 14 , nutritional parameters 15 , analytical values 16 , blood parameters 17 , and neutrophile to lymphocyte ratio can be measured by a blood test and the prognostic role of these variables is valuable.…”
Section: Introductionmentioning
confidence: 99%